ENHANCING THE PROFITABILITY OF A VERTICALLY INTEGRATED WOOD PRODUCTS PRODUCTION SYSTEM. PART 2. A CASE STUDY. - CARINO, HONORIO F. ; WILLIS III, DONALD B.
THIS PAPER PRESENTS THE RESULTS OF A CASE STUDY TO DEMONSTRATE THE EFFICACY OF LINEAR PROGRAMMING IN SOLVING A COMPLEX SET OF PRODUCTION-INVENTORY PROBLEMS FREQUENTLY FACED BY INTEGRATED WOOD PRODUCTS MANUFACTURING OPERATIONS.....